Life in motion : an unlikely ballerina - Copeland, Misty; Colbert, Brandy (Aladdin, 2016)
Determination meets dance in this middle grade adaptation of the New York Times bestselling memoir by the first African-American principal dancer in American Ballet Theatre history, Misty Copeland. Determination meets dance in this middle grade adaptation of the New York Times bestselling memoir by the first African-American principal dancer in American Ballet Theatre history, Misty Copeland. Life in Motion is a story for all the kids who dare to be different, dream bigger, and want to break stereotypes in whatever they do.